Hydralazine represses Fpn ubiquitination to rescue injured neurons via competitive binding to UBA52 - Shengyou Li; Xue Gao; Yi Zheng; Yujie Yang; Jianbo Gao; Dan Geng; Lingli Guo; Teng Ma; Yiming Hao; Bin Wei; Liangliang Huang; Yitao Wei; et al. (Elsevier, 2024)
A major impedance to neuronal regeneration after peripheral nerve injury (PNI) is the activation of various programmed cell death mechanisms in the dorsal root ganglion. Ferroptosis is a form of programmed cell death distinguished by imbalance in iron and thiol metabolism, leading to lethal lipid peroxidation. However, the molecular mechanisms of ferroptosis in the context of PNI and nerve regeneration remain unclear. Ferroportin (Fpn), the only known mammalian nonheme iron export protein, plays a pivotal part in inhibiting ferroptosis by maintaining intracellular iron homeostasis. Here, we explored in vitro and in vivo the involvement of Fpn in neuronal ferroptosis. We first delineated that reactive oxygen species at the injury site induces neuronal ferroptosis by increasing intracellular iron via accelerated UBA52-driven ubiquitination and degradation of Fpn, and stimulation of lipid peroxidation. Early administration of the potent arterial vasodilator, hydralazine (HYD), decreases the ubiquitination of Fpn after PNI by binding to UBA52, leading to suppression of neuronal cell death and significant acceleration of axon regeneration and motor function recovery. HYD targeting of ferroptosis is a promising strategy for clinical management of PNI.